FROM INFORMALITY TO PROFESSIONALIZATION: THE ROLE OF HR SYSTEMS IN FAMILY BUSINESS CONTINUITY - Martin Zebua; Bambang Sri Wibowo (JURNAL ILMIAH EDUNOMIKA, 2026)
The professionalization of human resource management systems in Indonesian SME family businesses faces a fundamental tension between the demands of modern management efficiency and the power of deep family logic. This study aims to uncover the specific mechanisms by which actors navigate these conflicting interests in the process of HRM formalization. A qualitative approach with a single case study design was applied to Abason, a consumer manufacturing company in the Central Java industrial area with fewer than 100 employees that is currently undergoing a second-generation transition. Data collection involved in-depth interviews with eight key informants, three months of participatory observation, and document analysis using triangulation and member checking validity strategies. The findings identified a model of ‘personalized formalization’: recruitment formalization operates through a ‘dual-track’ system that accommodates technical competence while maintaining the founder's internal pathway; the performance appraisal system produces ‘family-oriented KPIs’ that integrate quantitative targets with moral contributions; and succession planning takes place through informal mentorship that maintains founder control while building the capabilities of the second generation. The theoretical contribution lies in modifying the concept of Socioemotional Wealth by demonstrating the possibility of compatibility between the preservation of family values and the adaptation of modern systems in the context of Indonesian collectivism, rather than the binary trade-off assumed by Western literature. The practical implications emphasize the importance of ‘formalization with a local face’ and ‘co-leadership’ strategies for SME owners, while the policy implications indicate the need for mentoring programmed that are sensitive to the socio-emotional dynamics behind formal administrative requirements.